Mind the Gap: Reporting and Analysis of Sex and Gender in Health Research in Australia, a Cross-Sectional Study - Lea Merone; Komla Tsey; Darren Russell; Cate Nagle (Mary Ann Liebert, 2022)
Introduction: Historically, medical studies have underrepresented female participants and most research data have been collected from males and generalized to other genders. This article aims to determine if there is a sex and/or gender gap in recent Australian health research. Methods: This descriptive cross-sectional study of the published literature examines recent Australian-based clinical trials for inclusion of sex and gender. Medians and interquartile ranges (IQRs) were calculated for study sample sizes and female:male representation. Proportion of sex and/or gender was analyzed by the clinical specialty of the trials. t-Tests were used to ascertain significance of any difference in recruitment of female and males. Results: A total of 88 articles were included in the analysis. Most studies (n?=?63) were randomized clinical controlled trials. Overall women constituted 55% (IQR 30% of all participants). Of the 71 mixed-sex studies, only 8.9% (n?=?7) analyzed the data by sex. Women were significantly underrepresented in cardiology and nephrology studies and overrepresented in psychiatry, care of the elderly, and orthopedic studies. Conclusions: When analyzed by specialty, women are overrepresented in specialties considered to be female patient dominated, such as psychiatry and care of the elderly, and underrepresented in specialties such as cardiology and nephrology. The overrepresentation of women in some specialties can reinforce gender stereotypes, potentially harming women. In addition, exclusion of males from these areas of research may be of disservice to men's health.